Two-sex culling model-An application to cattle growth - GOYAL, V K; GUPTA, S C; PURI, P D; SHARMA, R C (The Indian Journal of Animal Sciences, 2013)
A two-sex model is developed to study the growth of a culling population of Hariana cattle, The growth in a cattle herd has been discussed under varying culling rates.